Interval Prediction Method for Wind Speed Based on ARQEA Optimized by Beta Distribution and SWLSTM - Sun, Zhenao; Shen, Yongshan; Chen, Zhe; Teng, Yun; Qian, Xiaoyi (Frontiers in Energy Research, 2022)
The interval prediction of wind speed is crucial for the economic and safe operation of wind farms. To overcome the probability density function parameter optimization and long-term correlation of time series problems in an interval prediction method, a hybrid model based on the beta distribution of an allele real-coded quantum evolutionary algorithm (ARQEA) and a shared weight long short-term memory neural network (SWLSTM) is proposed for predicting the interval of short-term wind speed, which is beta-ARQEA-SWLSTM. Input variables are determined via autocorrelation functions, and the shape and position parameters in the beta distribution function are optimized by the ARQEA algorithm. An interval-divided multi-distribution function aggregation is proposed to deal with the fluctuation of wind speed series. Lastly, case studies are provided to demonstrate the effectiveness of the proposed method.